The synthesis of Paris saponin VII mainly occurs in leaves and is promoted by light intensity - Wen, Feiyan; Chen, Siyu; Wang, Yue; Wu, Qinghua; Yan, Jie; Pei, Jin; Zhou, Tao (Frontiers in Plant Science, 2023)
Unraveling the specific organs and tissues involved in saponin synthesis, as well as the light regulatory mechanisms, is crucial for improving the quality of artificially cultivated medicinal materials of Paris plants. Paris saponin VII (PS VII), a high-value active ingredient, is found in almost all organs of Paris plant species. In this study, we focused on Paris polyphylla var. yunnanensis (Franch.) Hand. - Mzt. (PPY) and found that PS VII synthesis predominantly occurs in leaves and is increased by high light intensity. This intriguing discovery has unveiled the potential for manipulating non-traditional medicinal organ leaves to improve the quality of medicinal organ rhizomes. The analysis of the impact of organ differences on saponin concentration in P. polyphylla var. chinensis (Franch.) Hara (PPC), P. fargesii Franch. (PF), and PPY revealed consistency among the three Paris species and was mainly dominated by PS VII. Notably, the leaves and stems exhibited much higher proportions of PS VII than other organs, accounting for 80–90% of the four main saponins. Among the three Paris species, PPY had the highest concentration of PS VII and was selected for subsequent experiments. Further investigations on saponin subcellular localization, temporal variation, and stem wound fluid composition demonstrated that PS VII is synthesized in mesophyll cells, released into the intercellular space through exocytosis, and then transported to the rhizome via vascular tissue. These findings confirm the significant role of leaves in PS VII synthesis. Additionally, a 13C-glucose feeding to trace PS VII biosynthesis revealed that only PS VII in the leaves exhibited incorporation of the labeled carbon, despite conducting 13C-glucose feeding in leaves, stems, rhizomes, and roots. Thus, the leaves are indeed the primary organ for PS VII synthesis in PPY. Furthermore, compared with plants under 100 μmol m−2 s−1, plants under 400 μmol m−2 s−1 exhibited a higher PS VII concentration, particularly in the upper epidermal cells of the leaves. We propose that high light intensity promotes PS VII synthesis in leaves through three mechanisms: (1) increased availability of substrates for saponin synthesis; (2) protection of leaves from high light damage through enhanced saponin synthesis; and (3) enhanced compartmentalization of saponins within the leaves, which in turn feedback regulates saponin synthesis.